LAGU KAULINAN BARUDAK SEBAGAI MATERI PENGEMBANGAN MOTORIK BAGI SISWA TK PGRI MARGAJAYA TASIKMALAYA - Sukmana, Ari Fitriani (2017)
The titled study, "Kaulinan Barudak Song as Media of Psychomotor Development for PGRI Kindergarten students in Margajaya Tasikmalaya", has purpose to describe the method, the stages of learning, and the presented song material applies the Kaulinan Barudak song as a media for Psychomotor kindergarten. To explore the data, the researcher used descriptive analysis method by qualitative approach that analyzed through observation, interviews, documentation, and literature studies. The result of this study shows that the method used to convey the song based on: storytelling, methods of conversing, playing method, and the sociodramas method/ play a role. Besides, these stages of learning do not only begin from planning, implementation, and evaluation stage; but also the games have essences for the child to have intelligent brain, her body to be supple and smooth soul, so that she grows into a good personal character. The material used in the form kawih kaulinan (game songs) is titled hayam Jeung careuh, and oray-orayan. In the process of implementation, the election materials examine the aspects of` scope, sequence, continuity and balance. Furthermore, the child can interpret the taught songs character by means of the philosophy of the particular song.